COMPARATIVE PAIN SATISFACTION WITH TRANSFORAMINAL EPIDURAL STEROID INJECTION PLUS CAUDAL EPIDURAL STEROID INJECTION WITH CATHETER VERSUS TRANFORAMINAL EPIDURAL STEROID INJECTION PLUS LUMBAR INTERLAMINAR EPIDURAL STEROID INJECTION IN PATIENTS HAVING LOW BACKACHE WITH RADICULOPATHY OR RADICULAR PAIN - WAHEED, H; SAQIB, M; MUFTI, SS; MUSHTAQ, S; GHAFOOR, AUR; BASHIR, K (Biological and Clinical Sciences Research Journal, 2024)
Epidural steroid injections (ESI) have been used to treat radicular pain. However, no prospective research has been undertaken to determine the benefits associated with combining different epidural steroid injection techniques. Objective: This study was conducted to assess the efficacy of combining transforaminal epidural steroid injection (TFESI) with caudal epidural steroid injection (CESI) versus TFESI with interlaminar epidural steroid injection (ILESI) on patient pain, anxiety, and disability status in individuals suffering from radicular pain. Methods: A cross-sectional study was conducted in the National Hospital & Medical Centre Lahore from September 2022 to September 2023. Eighty patients with low backache and radicular pain who met the inclusion criteria were enrolled. The patients were randomly divided into Group A (TFESI + CESI, n=40) and Group B (TFESI + ILESI, n=40). Baseline demographic data were collected, and pain, anxiety, and disability were assessed using the Numerical Rating Scale (NRS), Hamilton Anxiety Scale, and Oswestry Low Back Disability Index, respectively. These parameters were measured at baseline, 2 weeks, 4 weeks, and 12 weeks post-intervention. Data were analysed using SPSS software, with comparisons made using the independent t-test and chi-square test, and a p-value of <0.05 considered statistically significant. Results: The mean age of the patients in Group A was 59.4 ± 10.2 years, while in Group B, it was 57.6 ± 11.1 years. Most patients were females, accounting for 58 (72.5%) of the study population. There was a significant decrease in the mean NRS score at 2, 4, and 12 weeks compared to the baseline value in Group B (p=0.01). Similarly, the mean Hamilton Anxiety Score and Oswestry Disability Score were significantly reduced after the intervention in Group B (p=0.04, p=0.01, respectively). Comparable findings were observed in Group A, with significant decreases in the mean NRS score at 2, 4, and 12 weeks (p=0.02) and substantial reductions in the Hamilton Anxiety Score and Oswestry Disability Score (p=0.001, p=0.03, respectively). Conclusion: This study found that combining CESI and TFESI with catheter offered a slightly more effective pain reduction than TFESI and ILESI after 12 weeks. The clinical effects of combining CESI with TFESI were similar to those of combining TFESI with ILESI in treating radicular pain. Both methods significantly reduced pain scores and improved anxiety and disability status in both groups.